2018
DOI: 10.1111/imb.12392
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, expression pattern and metabolic activity of flavin‐dependent monooxygenases inSpodoptera exigua

Abstract: Enhanced detoxification is one of the important mechanisms for insecticide resistance. Most research in this field to date has focused on the role of cytochrome P450s. Our previous work revealed that flavin-dependent monooxygenases (FMOs) were involved in metabolic resistance of Spodoptera exigua. In the present study we investigated the molecular characteristics, expression patterns and oxidative activities of SeFMO on insecticides. Three FMO genes, which encode proteins with the typical FMO motifs, were clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…From an applied perspective it would also provide a marker linked to PxFMO2 overexpression that could be used to develop diagnostics with which to monitor for this resistance mechanism in the field. Finally, previous work on S. exigua showed that exposure to several insecticides, including chlorantraniliprole, induces the expression of SeFMO1-3 (Tian et al, 2018). Given this finding it will be interesting in future to explore the potential of diamide insecticides to induce PxFMO2 and establish the relative importance of induced versus constitutive mechanisms in the upregulation of this gene in the HAW strain.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…From an applied perspective it would also provide a marker linked to PxFMO2 overexpression that could be used to develop diagnostics with which to monitor for this resistance mechanism in the field. Finally, previous work on S. exigua showed that exposure to several insecticides, including chlorantraniliprole, induces the expression of SeFMO1-3 (Tian et al, 2018). Given this finding it will be interesting in future to explore the potential of diamide insecticides to induce PxFMO2 and establish the relative importance of induced versus constitutive mechanisms in the upregulation of this gene in the HAW strain.…”
Section: Discussionmentioning
confidence: 78%
“…Work on beet armyworm, Spodoptera exigua , described modest increases (1.5-fold) in FMO activity and synergism with the FMO inhibitor methimazole (synergism ratio = 1.9) in a strain with resistance to metaflumizone a voltage-dependent sodium channel blocker (Tian et al, 2014). In a follow on study SeFMO1 , SeFMO2 and SeFMO3 were found to be overexpressed in the metaflumizone resistant strain compared to a susceptible strain, and functional expression of the three FMOs, followed by indirect assessment of their metabolic capacity, suggested they have activity against metaflumizone and lambda-cyhalothrin (Tian et al, 2018). Beyond these studies the primary focus of research on insect FMOs has been investigation of their role in detoxification of plant secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The open reading frame (ORF) of peroxidasin was cloned into pFastBac1 shuttle vector and then expressed in Sf9 cells using Bac‐to‐Bac Baculovirus Expression System (Thermo Fisher Scientific, USA) according to the protocol reported previously (Tian et al ., 2018). In brief, the ORF of peroxidasin with a 6× His‐Tag (CATCATCACCATCACCAT) for SDS‐PAGE detection and Ni‐column purification were amplified, ligated to pFastBac1 as the recombinant shuttle plasmid, and then transformed into DH10Bac cells.…”
Section: Methodsmentioning
confidence: 99%